Problematics of Disparity in Law Enforcement of Corruption: Influence Review and Law Reformulation Ideas - Iza Rumesten; Muhammad Syaifuddin; Taufani Yunithia Putri; Desia Rakhma Banjarani (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
Various controversies when disparities occur cannot simply eliminate it, this is because disparities are something that cannot be avoided from the freedom of judges in making decisions. Therefore, in order for the disparity to be directed towards realizing justice, it is necessary to have an ideal formulation of the disparity in corruption crimes in enforcing national law based on Pancasila values. Based on this background, the authors will conduct research with the formulation of the problem, namely: What is the effect of the disparity in corruption criminal decisions on the effectiveness of national corruption criminal law enforcement? What is the idea reformulation of the disparity in corruption decisions? Normative legal research using a statutory approach is the methodology employed in this study. The findings of the study show that the disparity in corruption decisions has an influence on the effectiveness of national corruption criminal law enforcement. The disparity in corruption criminal decisions can affect the public's perspective and evaluation of justice which can be seen as a disturbing form of injustice. Therefore, it is necessary to have a new formulation in sentencing which is the basis for judges in determining sentencing based on Pancasila as the ideology of the Indonesian state. The idea formulation of the disparity in corruption crimes in enforcing national law based on Pancasila values can be grouped as follows: formation of sentence guidelines; revision of the corruption law; improving the quality of institutions and law enforcement.